Predisposing factors and outcome of acute kidney injury in neonates - Ramesh, S (Indian Journal of Child Health, 2018)
Introduction: Acute kidney injury (AKI) influences the risk of mortality in sick neonates. Predicting AKI on the basis of risk factors may help in early intervention and improved outcome. Objective: The aim of this study is to identify the predisposing factors, clinical features, and outcome of AKI in neonates. Methodology: A retrospective study was carried out from September 2011 to August 2015. AKI was diagnosed if any one of the following is present: (1) Baby’s serum creatinine more than 1.5 mg/dl for at least 24–48 h with normal maternal renal function, (2) baby’s serum creatinine increases by more than 0.3 mg/dl over 48 h. All babies with AKI during the study were included in the study. Result: Twenty-five babies with AKI were studied. Male predominance was seen. Babies presented at a median age of 3 days interquartile range ([IQR] 2–5)with the median gestational age of 36 weeks (IQR 28–40) and median birth weight of 2490 g (IQR 1885–2875). Perinatal asphyxia (44%), blood culture positive sepsis (24%) and excess weight loss due to inadequate feeds (20%) were common causes for AKI. About half of the cases have received mechanical ventilation and/or inotropes. Nephrotoxic drug exposure was seen in 44% of cases. Only one-third of the babies had oliguria. Fluid boluses, diuretics, and sodium bicarbonate to correct acidosis were commonly used for medical management. Only 12% of cases required peritoneal dialysis. One baby expired. Conclusion: Perinatal asphyxia, sepsis, excess weight loss, and cardiopulmonary compromise predisposes to AKI in neonates. Many babies improve with medical management.